Synthesis and electrocatalytic properties of polymerizable metallophthalocyanines - Obirai, Joseph Chinye (Rhodes University, Faculty of Science, Department of Chemistry, 2005)
The syntheses, spectral and electrochemical characterization of new family electropolymerizable pyrrole, thiophene and mercaptopyrimidin substituted metallophthalocyanine (MPc) complexes are described. Tetraamino substituted chromium and manganese phthalocyanine complexes were also synthesized and characterized. The spectral and electrochemical results are comparable to literature reports. The complexes formed stable films when deposited on electrode surfaces. The MPc films were formed by electropolymerization, drop-dry method and self-assembling. Nickel hydroxide-like electrodes were formed by electrotransformation of nickel-tetra-4- (pyrrol-1-yl)phenoxy phthalocyanine polymer films to the corresponding PcNi-O-NiPc modified electrodes in alkaline solution. The thiophene, mercaptopyrimidine functionalized MPcs and amino group containing complexes formed good self-assembled monolayers (SAMs) on gold electrode. The electrode modification processes were reproducible. The conductivities of the electrode were dependent on the surface concentrations of the complexes as a function of electropolymerization scan numbers. The electrodes showed good catalytic responses toward L-cysteine, nitrite, nitric oxide (NO), glycine, phenol and its derivative and oxygen. The results also suggest that the presence of thio groups on the ring substituents lowers the oxidation potential of Lcysteine more compared to literature values. The stability of the amperometric responses toward the various analytes is used to diagnose the applicability of the materials for electroanalytical purposes. The limits of detection for L-cysteine, nitrite, NO and glycine were in the range of ~10â »â · to 10â »â µ mol dmâ »Â³.
Keywords: Phthalocyanines; Electrochemistry